EL SERAFY’S TEMPLATE FOR NONRENEWABLE-RESOURCE ACCOUNTING - Cairns, Robert (L'Actualité économique)

(untitled) (HEC Montréal, 2019)
In 1989, Salah El Serafy proposed a method of accounting for a nonrenewable resource based on net present value. A reinterpretation and extension of his analysis permit what he calls a proper representation of net income for use in an accurate aggregation, “bottom-up”, from project or enterprise data to the sectorial and national accounts. An earlier paper by Lasserre provides intellectual support for the method. What may be called El Serafy’s template can be interpreted and applied for many purposes, including the proper calculation of income and depletion of an exhaustible resource.